Vertical structure of very nearshore larval fish assemblages in a temperate rocky coast - Borges, Rita Alexandra (2007)
Small-scale vertical patterns of larval distribution were studied at a very nearshore larval Wsh assemblage, during the spring–summer period of several years, at two depth strata (surface and bottom) using sub-surface and bottom trawls. A total of 4,589 larvae (2,016 from surface samples and 2,573 from bottom samples) belonging to 62 taxa included in 22 families were collected. Most larvae belonged to coastal species. Although inter-annual variations in larval density and diversity could be found, total larval abundance was always higher near the bottom whereas diversity was higher at the surface. A marked distinction between the structure of surface and bottom assemblages was found. Sixteen taxa explained 95% of the similarity among surface samples. Larvae which contributed most to this similarity included species like clupeiformes, sparids and serranids, and also blenniids, tripterygiids and some labrids. In the bottom samples, fewer species were present, with only six taxa, almost exclusively from species which lay demersal eggs, contributing to 95% of the similarity between samples. Larvae present at the surface were signiWcantly smaller than at the bottom. For some of the most abundant species found at the bottom, only small larvae occurred at the surface while the whole range of sizes was present at the bottom, indicating that larvae may be completing the entire pelagic phase near the adults’ habitat. These results indicate that larval retention near the reefs probably occurs for these species, although for others dispersal seems to be the prevailing mechanism.